2018
DOI: 10.1186/s12872-018-0784-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes associated with catecholamine use in patients diagnosed with Takotsubo cardiomyopathy

Abstract: BackgroundRecent hypotheses have suggested the pathophysiological role of catecholamines in the evolution of the Takotsubo syndrome (TTS). The extent of cardiac and circulatory compromise dictates the use of some form of supportive therapy. This study was designed to investigate the clinical outcomes associated with catecholamine use in TTS patients.MethodsOur institutional database constituted a collective of 114 patients diagnosed with TTS between 2003 and 2015. The study-patients were subsequently classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 32 publications
0
24
0
2
Order By: Relevance
“…The microvascular dysfunction caused by catecholamines has been proposed as part of the unifying mechanism of TC [4]. This fact is supported by the evidence that the administration of adenosine, a potent vasodilator, temporarily resolves perfusion and wall motion abnormalities in TC [8].…”
Section: Reviewmentioning
confidence: 89%
See 2 more Smart Citations
“…The microvascular dysfunction caused by catecholamines has been proposed as part of the unifying mechanism of TC [4]. This fact is supported by the evidence that the administration of adenosine, a potent vasodilator, temporarily resolves perfusion and wall motion abnormalities in TC [8].…”
Section: Reviewmentioning
confidence: 89%
“…In cases of TC, the use of catecholamines for acute circulatory support may have deleterious effects and their use is associated with increased mortality [4,26]. Therefore, the need for circulatory support should be balanced with a potential causative role of catecholamines in TC.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 4,313 articles were found of which 248 articles met the inclusion criteria. Based on predefined criteria, only 16 of these articles were included in this review ( Table 1) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Literature Search and Data Sourcementioning
confidence: 99%
“…Cardiogenic shock with LVOTO: In patients with cardiogenic shock with moderate to severe LVOTO, inotropic agents should not be used because they can increase the degree of obstruction [31,34]. In a study by Ansari et al, it was reported that inotropes such as epinephrine, norepinephrine, dobutamine, and dopamine should be avoided in TTS, and that catecholamine excess can increase 30-day and long-term mortality in TTS [9]. Only Marfella et al reported that alpha-adrenergic stimulation by alpha-lipoic therapy could increase sympathetic stimulation of the heart and show improvement of cardiac defects on 123Imetaiodobenzylguanidine myocardial scintigraphy at a 12-month follow-up in TTS patients [7].…”
Section: Tts With Complications -Hypotension and Cardiogenic Shockmentioning
confidence: 99%